2021
DOI: 10.1101/2021.02.04.21251169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DrugWAS: Leveraging drug-wide association studies to facilitate drug repurposing for COVID-19

Abstract: Importance: There is an unprecedented need to rapidly identify safe and effective treatments for the novel coronavirus disease 2019 (COVID-19). Objective: To systematically investigate if any of the available drugs in Electronic Health Record (EHR), including prescription drugs and dietary supplements, can be repurposed as potential treatment for COVID-19. Design, Setting, and Participants: Based on a retrospective cohort analysis of EHR data, drug-wide association studies (DrugWAS) were performed on COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…An important finding by our study is that recent exposure to various types of Streptococcus pneumoniae vaccines and diphtheria toxoid and tetanus toxoid vaccine, with or without acellular pertussis vaccine, is associated with a decreased risk of death and other severe COVID‐19 outcomes. This finding replicates the results of our preliminary analysis on 7,768 patients infected with SARS‐CoV‐2 41 . Recently, Streptococcus pneumoniae vaccines were also found to have a protective effect against COVID‐19 outcomes suggesting that pneumococci may interact with SARS‐CoV‐2 in the respiratory tract 42 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An important finding by our study is that recent exposure to various types of Streptococcus pneumoniae vaccines and diphtheria toxoid and tetanus toxoid vaccine, with or without acellular pertussis vaccine, is associated with a decreased risk of death and other severe COVID‐19 outcomes. This finding replicates the results of our preliminary analysis on 7,768 patients infected with SARS‐CoV‐2 41 . Recently, Streptococcus pneumoniae vaccines were also found to have a protective effect against COVID‐19 outcomes suggesting that pneumococci may interact with SARS‐CoV‐2 in the respiratory tract 42 .…”
Section: Discussionsupporting
confidence: 89%
“…This finding replicates the results of our preliminary analysis on 7,768 patients infected with SARS‐CoV‐2. 41 Recently, Streptococcus pneumoniae vaccines were also found to have a protective effect against COVID‐19 outcomes suggesting that pneumococci may interact with SARS‐CoV‐2 in the respiratory tract. 42 A double‐blind placebo‐randomized trial showed that the pneumococcal conjugate vaccine protects children against pneumococcal coinfections with seasonal coronaviruses.…”
Section: Discussionmentioning
confidence: 99%